Rheological properties and ageing of bioslurry fuels prepared from crude glycerol/methanol/bio-oil blend and biochar for stationary combustion applications - Gao, W.; Zhang, Mingming; Wu, Hongwei (2017)
© 2018 Combustion Institute. All Rights Reserved. This study investigates the rheological properties and ageing of bioslurry fuels prepared from crude glycerol/methanol/bio-oil (FCGMB) blend and biochar, benchmarking against the glycerol/methanol/bio-oil/biochar (GMBB) bioslurry for stationary combustion applications. Both FCGMB/biochar (FCGMBB) bioslurry and GMBB bioslurry fuels exhibit non-Newtonian and thixotropic behavior. The viscosities of FCGMBB bioslurry fuels are 222–268 mP.s which are lower than that of GMBB bioslurry due to the presence of water in formulated crude glycerol (FCG). Ageing leads to decreases in the total acid number (TAN) and viscosity but an increase in water content of both FCGMBB and GMBB bioslurry fuels due to various reactions. The changes of the water content (4.4–4.8%) and viscosity (6.0–11.7%) of FCGMBB, and the TAN (2.6% and 4.3%) of FCG1MBB/FCG3MBB bioslurry fuels before and after ageing are lower than that of GMBB bioslurry. This is due to the presence of soap and NaOH in FCGs. Overall, FCGMBB bioslurry fuels have better rheological property than GMBB bioslurry, and the presence of crude glycerol in the FCGMBB slurry fuels slows down the ageing.